Mechanism of Microscopic Fracture of Typical Shell Steel under Impact Loading - Chuan Zhao; Shushan Wang; Cean Guo; Yuhui Sun; Xuncheng Guo; Feng Ma (Shock and Vibration)
The aim of the current study was to investigate the effects of strain rate and metallographic structure on the fracture mode and fracture pattern of a typical shell steel material under impact loading. A ballistic gun was used to launch a spherical tungsten alloy projectile to impact target 50SiMnVB and 60Si2Mn steel plates. The morphological characteristics of the cracks on different target plates were observed under a metallurgical microscope, and the effects of the strain rate and metallographic structure on the fracture mode and fracture pattern were analyzed. The results showed that when the strain rate was relatively low, the material mainly produced ductile fracture and brittle trans-granular fracture under impact loading; when the strain rate was relatively high, intergranular fracture and cleavage fracture were the main modes of fracture under impact loading. In addition, at higher strain rates, the metallurgical form mainly influenced the pattern of fracture of the material, with tempered troostite being more likely to produce a mixture of shear and tensile fractures than tempered sorbite. The results obtained provide an experimental basis for the mechanism of microscopic fracture of shell steel materials and, to a certain extent, reveal the correlations between fragmentation and the strain rate and microstructure of the material.